Reinforcement Design of Transfer Beams in a three-Story Residential Building - Usnawa, Hamid Wafiq; Soelarso, Soelarso; Baehaki, Baehaki; Darwis, Zulmahdi; Rahma, Midia (Jurnal Fondasi, 2025)
Residential buildings are buildings that are used as residences, for example, houses. In residential buildings that carry modern aesthetics will make the shape of the plan tend to be irregular, so it is necessary to adjust structural elements such as slender columns and transfer columns. A transfer column is a column that rests on a beam (grows across the beam), so the column is not continuous from the bottom floor to the top, while the beam is called a transfer beam. Transfer beams allow load distribution from the upper floors to the structural elements below. This study was conducted to determine the reinforcement requirements of transfer beams in a three-story residential building in accordance with SNI 2847: 2019. Structural analysis was carried out with the ETABS v9.7.1 program and manual calculations to determine the reinforcement configuration of the transfer beam. The result of the research is that the transfer beam with dimensions of 350 mm x 650 mm has a reinforcement configuration, namely 4D19 tensile and 6D19 compressive reinforcement in the support area, and 12D19 tensile and 6D19 compressive reinforcement in the field area, for stirrup reinforcement used 3D12 - 100 mm and for torsion reinforcement used 2D16. As for the deflection that occurs, which is 7,782 mm, this value is still within the permit limit according to SNI 2847: 2019. It can be concluded that the transfer beam is safe to use.